Verification: model-free phasing with enhanced predicted models in ARCIMBOLDO_SHREDDER - Medina, Ana; Jiménez, Elisabet; Caballero, Iracema; Castellví, Albert; Triviño Valls, Josep; Alcorlo, Martin; Molina, Rafael; Hermoso, Juan A.; Sammito, Massimo D.; Borges, Rafael [UNESP]; Usón, Isabel (International Union of Crystallography (IUCr), 2022)
Structure predictions have matched the accuracy of experimental structures from close homologues, providing suitable models for molecular replacement phasing. Even in predictions that present large differences due to the relative movement of domains or poorly predicted areas, very accurate regions tend to be present. These are suitable for successful fragment-based phasing as implemented in ARCIMBOLDO. The particularities of predicted models are inherently addressed in the new predicted_model mode, rendering preliminary treatment superfluous but also harmless. B-value conversion from predicted LDDT or error estimates, the removal of unstructured polypeptide, hierarchical decomposition of structural units from domains to local folds and systematically probing the model against the experimental data will ensure the optimal use of the model in phasing. Concomitantly, the exhaustive use of models and stereochemistry in phasing, refinement and validation raises the concern of crystallographic model bias and the need to critically establish the information contributed by the experiment. Therefore, in its predicted_model mode ARCIMBOLDO_SHREDDER will first determine whether the input model already constitutes a solution or provides a straightforward solution with Phaser. If not, extracted fragments will be located. If the landscape of solutions reveals numerous, clearly discriminated and consistent probes or if the input model already constitutes a solution, model-free verification will be activated. Expansions with SHELXE will omit the partial solution seeding phases and all traces outside their respective masks will be combined in ALIXE, as far as consistent. This procedure completely eliminates the molecular replacement search model in favour of the inferences derived from this model. In the case of fragments, an incorrect starting hypothesis impedes expansion. The predicted_model mode has been tested in different scenarios.
Keywords: AlphaFold; ARCIMBOLDO; ARCIMBOLDO_SHREDDER; fragment-based molecular replacement; model bias; phasing; predictions; RoseTTAFold; verification